(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article is filled with information about substances affecting the muscles of the uterus, their side effects, pharmacokinetics, pharmacodynamics, and cases of use. In the article, substances that increase uterine muscles (oxytocinic): oxytocin, pituitrin, prostaglandins; substances that reduce the contraction of uterine muscles (tocolytics): salbutamol, fenoterol are discussed in detail.